2009
DOI: 10.1111/j.1533-8525.2008.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Crossracial Differences in the Racial Preferences of Potential Dating Partners: A Test of the Alienation of African Americans and Social Dominance Orientation

Abstract: Studying interracial romance has been useful for understanding general race relations. Theories of African American alienation and social dominance orientation help explain why previous research has found African Americans to be the least desired racial dating partners. Alienation predicts that African Americans are less willing to interracially date than other racial groups since they are not allowed to participate in the majority culture. Social dominance orientation predicts that African Americans are more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 75 publications
2
65
0
Order By: Relevance
“…Specifically, Hispanics and non-Hispanic Whites display a much weaker tendency toward homophily in marriages and friendships than do Black and Asian Americans, and Black Americans out-partner less than any other racial minority (Joyner & Kao, 2000;Kalmijn, 1993;Qian, 1997;Rosenfeld, 2002Rosenfeld, , 2008. These patterns are consistent with willingness to date interracially: When stating their preferences in online dating advertisements, Blacks are least willing to date a partner of any race (Yancey, 2009). Asians are most willing to date a partner of any race, but this may be explained by their small group size: Asians may relax their preferences for homophily in response to limited opportunities to meet other Asians.…”
Section: Introductionsupporting
confidence: 63%
“…Specifically, Hispanics and non-Hispanic Whites display a much weaker tendency toward homophily in marriages and friendships than do Black and Asian Americans, and Black Americans out-partner less than any other racial minority (Joyner & Kao, 2000;Kalmijn, 1993;Qian, 1997;Rosenfeld, 2002Rosenfeld, , 2008. These patterns are consistent with willingness to date interracially: When stating their preferences in online dating advertisements, Blacks are least willing to date a partner of any race (Yancey, 2009). Asians are most willing to date a partner of any race, but this may be explained by their small group size: Asians may relax their preferences for homophily in response to limited opportunities to meet other Asians.…”
Section: Introductionsupporting
confidence: 63%
“…Literature measuring social distance among various racial/ethnic groups has found that non-Black minorities hold higher social positions than Blacks but lower social positions than Whites [12]. Due to the history of enslavement and intense race relations in the U.S., the hierarchical racial/ethnic divide may be upheld most strongly between Blacks and Whites.…”
Section: Intercultural Marriage In the United Statesmentioning
confidence: 99%
“…Intercultural dating is a salient and high stakes issue for Latina and Black women attending predominantly White institutions (PWIs) [12]. Nationally, the college student population is about 65% female for Black students and 60% female for Latino/a students, compared to 55% female for White students [18].…”
Section: Intercultural Marriage In the United Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of teams have explored racial/ethnic preferences in speed and online dating, however, and results across studies suggest that most people report and exhibit less willingness to date inter-racially than intra-racially (e.g., Hwang, 2013;Kurzban & Weeden, 2005;Yancey, 2009). Past that generality, preferences are lessclear.Acrossthreestudies,non-Whiteindividualshadstronger preferences for intraracial partners (Kurzban & Weeden, 2005;Phua&Kaufman,2003;Yancey,2009)although,inanotherstudy, an interaction between race and gender emerged such that women of higher racial status groups (i.e., White) reported the least willingness to date interracially (Hwang, 2013).…”
Section: Introductionmentioning
confidence: 94%